Good Governance and Public Service Performance in Indonesia: A Secondary Data Analysis of Accountability, Digital Government, and Service Quality - Shelina Amalia; Abdul Sahid; Ambo Masse (Journal of Indonesian Scholars for Social Research, 2026)
Good governance is widely presented as a normative foundation for improving public-sector performance, yet its practical relationship with public service quality is not always straightforward. This study examines the implementation of good governance in Indonesian public service delivery using secondary data only. A descriptive-integrative secondary data design was employed by synthesizing official government statistics, regulatory documents, Ombudsman reports, international governance frameworks, and peer-reviewed literature. The principal empirical sources include the national Public Service Index (Indeks Pelayanan Publik/IPP), the Electronic-Based Government System Index (Sistem Pemerintahan Berbasis Elektronik/SPBE), the 2024 public service compliance assessment of the Ombudsman of the Republic of Indonesia, and national regulations governing public services and digital government. The results show measurable progress in several governance-related indicators. The national IPP increased from 3.93 in 2023 to 4.02 in 2024, while the national SPBE Index rose from 2.26 in 2020 to 3.12 in 2024. Ombudsman data also indicate that the number of assessed entities classified in the green zone increased from 179 in 2021 to 494 in 2024, representing approximately 84.16% of the 587 entities assessed in 2024. Nevertheless, more than 10,000 public reports were resolved and approximately 112,000 consultations were received by the Ombudsman during 2024, with local governments remaining the most frequently reported institutions. These findings suggest that Indonesia has strengthened formal compliance, service standards, and digital administrative capacity, but persistent complaints and maladministration risks reveal an implementation gap between institutional reform and citizens’ service experiences.